Students’ Learning Experiences in Nahwu Instruction at MAN 3 Cirebon: A Phenomenological Study of Problems and Learning Strategies - Sri Widiasari; Maman Rusman; Khasan Aedi (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
This study aims to comprehensively describe the problems and solutions in Nahwu instruction among Grade X students at MAN 3 Cirebon. The research focuses on the conceptual difficulties students experience and the factors that influence the learning process. A qualitative approach with a case study design was employed, using in-depth interviews and classroom observations involving thirty students. The results indicate that the students’ main difficulties fall into four categories: (1) confusion in distinguishing types of ḍamīr and identifying their referents, (2) difficulty in recognizing jamā‘ taksīr patterns due to the wide variety of wazn and morphological forms, (3) complexity in applying the rules of ‘adad–ma‘dūd, and (4) inability to determine i‘rāb resulting from weak foundational understanding of Nahwu. These difficulties are influenced by internal factors such as diverse educational backgrounds from Islamic boarding schools, limited experience with Nahwu, and students’ physical and psychological conditions, as well as external factors such as mismatched teaching styles and an unconducive classroom environment. The study also identifies several strategic efforts, such as scaffolding, rule visualization, and gradual practice, as recommendations for improving Nahwu instruction. Therefore, this study addresses a gap in previous research that has paid insufficient attention to students’ learning experiences through the perspective of the meanings they construct for themselves when facing difficulties in learning Nahwu.